Two Paediatric Patients with Encephalopathy and Concurrent COVID-19 Infection: Two Sides of the Same Coin?. (24th March 2021) - Vraka, Katerina; Ram, Dipak; West, Siobhan; Chia, Wei Yen Evelyn; Kurup, Praveen; Subramanian, Gayathri; Tan, Hui Jeen
Abstract : There is increasing evidence that SARS-CoV-2 has neurotropic potential. We report on two paediatric patients who presented with encephalopathy during COVID-19 illness. Both patients had ADEM-like changes in their neuroimaging, negative SARS-CoV-2 RNA PCR in CSF, and paucity of PIMS-TS laboratory findings. However, the first patient was positive for serum MOG antibodies with normal CSF analysis, and the second had negative MOG antibodies but showed significant CSF lymphocytic pleocytosis. We concluded that the first case was a typical case of demyelination, which could have been triggered by different cofactors. In the second case, however, we postulated that the encephalopathic process was triggered by SARS-CoV-2, as no other cause was identified. With these two contrasting cases, we provide evidence that SARS-CoV-2-associated encephalitis can show ADEM-like changes, which can present during the postinfectious phase of COVID-19 illness. As ADEM is a relatively common type of postinfectious encephalitis in children, the distinguishing line between the two conditions of encephalitis and ADEM can be relatively fine. The development of more reliable diagnostic tools (e.g., anti-SARS-CoV-2 antibodies in CSF) might play an assisting role in the differentiation of these encephalopathic processes.